A comparative analysis of selected attributes of four brands of longanisa - Mangubat, Ma. Rosario R.; del Valle, Mercedita (1978.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Sausages -- Analysis